The effect of decitabine on megakaryocyte maturation and platelet release - Wang, Jianhui; Yi, Zanhua; Wang, Shiyang; Li, Zongdong (Thrombosis and Haemostasis, 2011)
Thrombocytopenia is a common feature of myelodysplastic syndromes (MDS). 5-aza-2’-deoxycytidine (decitabine) has been used to treat MDS with an approximately 20% response rate in thrombocytopenia. However, the mechanism of how decitabine increases platelet count is not clear. In this study, we investigated the effect of decitabine on megakaryocyte maturation and platelet release in the mouse. The effect of decitabine on megakaryocyte maturation was studied in an in vitro megakaryocyte differentiation model utilising mouse bone marrow cells and mouse megakaryoblastic cell line L8057. Decitabine (2.5 μM) is able to induce L8057 cells to differentiate into a megakaryocyte-like polyploidy cells with positive markers of acetylcholinesterase and αIIb integrin (CD41). Higher expression of αIIb integrin was also found in primary mouse bone marrow cells and human cord blood CD34+ cells cultured with both thrombopoietin and decitabine as compared to thrombopoietin alone. In addition, we noted a 30% platelet count increase in Balb/c mice 12 hours after the injection of decitabine at a clinically relevant dose (15 mg/m2), suggesting a rapid platelet release from the spleen or bone marrow. Our data suggest that decitabine increases platelet counts by enhancing platelet release and megakaryocyte maturation.
Keywords: Myelodysplastic syndromes; decitabine; thrombocytopenia